2022-RA-798-ESGO Diagnosis of first relapse and its impact on quality of life in patients with advanced ovarian cancer (AGO-OVAR 19/II). (20th October 2022) - Harter, Philipp; Ataseven, Beyhan; Burges, Alexander; Reuss, Alexander; Kommoss, Stefan; Sehouli, Jalid; Lampe, Björn; Schmalfeldt, Barbara; Wimberger, Pauline; Witteler, Ralf; Buderath, Paul; Herwig, Uwe; et al.
Abstract : Introduction/Background: Maintenance or improvement of health-related quality of life (QoL) is a major goal for patients with advanced ovarian cancer (OC). QoL is influenced by symptoms on the one and effects of surgical and systemic treatment on the other side. In addition, QoL is also an important patient centered endpoint in trials to support endpoints such as progression-free survival (PFS). This analysis evaluates the impact of the diagnosis of first relapse on QoL. Methodology: Patients with primary OC were included before start of treatment. QoL was assessed by the cancer-specific questionnaires EORTC QLQ-C30 and QLQ-OV 28 and the generic EQ-5D 3L at baseline and every 3 months thereafter. QoL data within 100 days before and after the first relapse were compared (part 2 of NCT02828618 ). We report model-based pre- and post-recurrence means and p-values for the difference in means. Results: 269 of 486 enrolled patients had a PFS event resulting in a median PFS of 20.3 months. This analysis includes QoL-evaluable 186 patients. Median age was 62.5 years (range 31 – 90). The number of evaluable answers for each domain ranged between 166 and 172 before recurrence and 135 and 137 after recurrence. Global QoL decreased from 61.4 to 48.4 points (p<0.001) with the diagnosis of recurrence. The following scales showed a deterioration of at least 10 points: Social functioning (65.7-> 52.6), fatigue (44.5->55.8), appetite loss (22.5 -> 33.4), emotional functioning (65.2 -> 54.9), role functioning (56.5 -> 46.4); (all p<0.001). EQ-5D 3L visual analogue scale showed a deterioration from 66.4 to 55.0 (p<0.001). Conclusion: The event of first relapse is associated with a significant and clinically relevant deterioration of global QoL including several subscales. Therefore, prolongation of PFS preserves QoL, which supports the role of PFS as meaningful primary endpoint in ovarian cancer trials.